SOME OBSERVATIONS ON THE BIOLOGY OF COILIA BORNEENSIS (BLKR) - Varghese, T J (Indian Journal of Fisheries, 2011)
Coilia bomeensis, locally known as "Amadi," is a medium-sized clupeoidvery common in the estuaries of West Bengal. Day (1878) has recorded thespecies from Madras, Burma and the Malay Archipelago. The fish is moreabundant in the middle stretch of the estuarine system than in the upper andlower zones.Bag-net (Beenjal, Behundijal or Thorjal) is the main gear by whichC. bomeensis is caught, though it is also taken along with other fishes in thecatches of barrier-nets (Chorpatajal) and shore-seines (Berjal).